Fiscal Sustainability and Monetary Versus Fiscal Dominance : Evidence From Brazil, 1991-2000 - Tanner, Evan (IMF Working Papers; Working Paper ;, 2002)
Under a monetary dominant (MD) regime, the primary surplus adjusts to limit debt growth, permitting monetary policy to be conducted independently of fiscal financing requirements. In Brazil, some evidence favors an MD regime for 1995-97, but not for the decade of the 1990s as a whole. While fiscal adjustments of 1999 yielded a primary surplus of about 3 percent of GDP, consistent with solvency, a credible MD regime would require further adjustments of the primary surplus if debt increases, growth falls, or interest rates rise.